Análise do perfil da expressão de genes candidatos com a eficiência alimentar de animais da raça Nelore - Rosa, Kamila de Oliveira da [UNESP] (2015)
Brazil is one of the leading producer and exporter of meat. However, different livestock and plant production have been competing with cattle for space and importance in Brazilian trade balance. Thus, the animal breeding has played a key role in beef cattle to increase production levels occupying the same space at lower costs. Feed efficiency is a productive trait of extreme importance, but it has not been considered in genetic evaluation programs in our country. This is probably due to the fact that the measurement is costly and late. In this scenario molecular genetics may contribute to the implementation of this trait in breeding programs by identifying candidate genes for feed efficiency. The present study aimed to confirm the differential gene expression levels of candidate genes previously identified by RNA sequencing (RNA-seq) in extreme groups of animals evaluated for feed efficiency. We adopted the real time quantitative PCR methodology (qPCR) to verify a quantitative relationship between the level of gene expression and feed efficiency in an experimental population of 83 Nelore cattle evaluated for different feed efficiency traits. A subgroup composed of 20 animals extreme for Residual Feed Intake (RFI) was evaluated for overall standard of expression by RNA-seq technology to identify genes differentially expressed (DE). From the identified DE genes six candidate genes were selected (PPP1R26, FABP1, FADS2, RGS2, SLC2A5 and UCP2) based on fold change values and its metabolic function related to feed efficiency. The qPCR analyses were performed to confirm association between the expression level of the six target genes with measures of feed efficiency. It was observed association between the FABP1 gene with residual feed intake and dry matter intake (P <0.05). Also, the SLC2A5 gene was associated with Kleiber index measurements and relative growth rate (P <0.05). In both cases an increase in the expression level was associated ...